2003
DOI: 10.1002/chem.200305125
|View full text |Cite
|
Sign up to set email alerts
|

Azolylpentazoles as High‐Energy Materials: A Computational Study

Abstract: The structures of highly energetic substituted pentazole compounds and their decomposition to give dinitrogen and the corresponding azide were investigated by ab initio quantum chemical methods. The substituents include azolyl groups (five-membered aromatic rings with different numbers of nitrogen atoms), CH(3), CN, and F. The decomposition pathway was followed for several substituted azolyl- and phenylpentazoles and compared to the known experimental and theoretical results. The NMR parameters of most of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
22
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 87 publications
4
22
0
Order By: Relevance
“…Theoretical studies [23,24] identified at least six vibrationally stable isomers of FN 5 but, in accordance with experimental results, the predicted lifetimes of these species are only in the nanosecond range. [23] During attempts to prepare N …”
Section: F]supporting
confidence: 78%
“…Theoretical studies [23,24] identified at least six vibrationally stable isomers of FN 5 but, in accordance with experimental results, the predicted lifetimes of these species are only in the nanosecond range. [23] During attempts to prepare N …”
Section: F]supporting
confidence: 78%
“…Previous studies on several neutral azoles, including triazole, tetrazole, and pentazole, show that the activation energies for this family of azoles depend on the number of ring nitrogen atoms and increase in the order pentazole < tetrazole < triazole. 27 It is expected that their monosubstituted cationic counterparts will follow the same trend. Table 12 shows that EDGs in isomer I such as -CH 3 , -CH 2 -NO 2 , and -C 2 H 3 tend to give the largest activation energies (24.0, 22.6. and 21.8 kcal/mol, respectively) while EWGs such as -N 3 (16.0 kcal/mol) and -CN (19.0 kcal/mol) give the smallest barriers.…”
Section: Resultsmentioning
confidence: 99%
“…[31] The stability of tetrazolylpentazole and its corresponding anion pentazolyltetrazolate was calculated to be 15-16 and 21-22 kcal mol À1 , respectively, using B3PW91 and MP2 calculations, [31] and later to be 11.4 and 17.7 kcal mol À1 , respectively, using CCSD(T) calculations. [32] An interesting and poorly understood molecule in the pentazole family, with possible applicability as an HEDM, is the cyclic oxopentazole anion (ON 5 À , c.f. 4 in À (X = S, Se, and Te) derivatives.…”
Section: Pentazolesmentioning
confidence: 99%
“…[33] Hammerl et al have investigated the isoelectronic neutral FN 5 molecule using CCSD(T) calculations, and predicted a decomposition barrier of 6.7 kcal mol À1 . [32] Very recently, Noyman et al investigated the effect of separating the s and p molecular orbitals (MOs) of polynitrogen systems by introducing oxygen atoms. [34] Among other things they concluded that coordination of oxygen to the nitrogen ring system of pentazolate (3) did not stabilize the molecule (i.e., oxopentazolate, 4).…”
Section: Pentazolesmentioning
confidence: 99%